Soil Moisture Characteristics of Indian Grumosols as Related to Wheat Production under Unirrigated Conditions - Tiwari, Y D; Singh, T A; Tamboli, P M (Annals of Arid Zone, 2016)
Field experiments were conducted durin2 the years 1964 to 1967 in Jabalpur to test the 'haveli' system of wheat cultivation, wherein the water is stored by bunding the fields during the monsoon season and wheat crop is taken in the rabi season, after draining the standing water. The soil under experimentation is classified as Kheri clay (Grumosol) and has very poor hydraulic conductivity (0.125 cm/hr in the 0-22.5 em depth layer). Results indicated that more moisture was stored in the bunded treatment when compared to the unbunded one. During rabi season the top layer (0-22.5 em) was depleted more due to evapotranspiration. Data also indicate that even when less than 50 per cent of the normal rainfall occurs, bunding stores more moisture and gives higher yields in comparison to unbonded fields,